Nonlinear magnetoquasistatic interface problem in a permanent-magnet machine with stochastic partial differential equation constraints. Issue 12 (2nd December 2019) - Putek, Piotr
ABSTRACT: This study discusses an application of the stochastic collocation method for the solution of a nonlinear magnetoquasistatic interface problem that is constrained by a partial differential equation with random input data. Special attention is given to finding the robust design of a rotor and a stator of an electrical machine for the reduction of electromagnetic losses and a cogging torque under material uncertainties. For this reason, variations of material properties are modelled using the polynomial chaos expansion technique. To develop the domain derivative of a robust cost functional, the velocity method is applied with an adjoint technique. The utility and efficiency of the proposed method has been successfully demonstrated by applying it to the design of a permanent-magnet synchronous machine used in electric vehicles.